Biochemical and proteomic effects in Procambarus clarkii after chlorpyrifos or carbaryl exposure under sublethal conditions - Vioque-Fernandez, Amalia; de Almeida, Eduardo Alves [UNESP]; Lopez-Barea, Juan (Taylor & Francis Ltd, 2009)
In vivo effects of two sublethal doses of chlorpyrifos and carbaryl were studied in Procambarus clarkii after 2 and 7 days of exposure, and after pesticide removal. Chlorpyrifos inhibited carboxylesterase activity in a concentration-dependent manner, but acetylcholinesterase was less sensitive. Compared with chlorpyrifos, carbaryl had a less marked effect on esterase activity. The effects of selected pesticides on biotransformation or oxidative stress biomarkers were contradictory. Chlorpyrifos lowered ethoxyresorufin-O-deethylase (EROD), catalase and oxidized glutathione (GSSG) levels but raised glutathione-S-transferase activity, while carbaryl raised EROD, catalase and glutathione-S-transferase, but lowered glutathione peroxidase and reduced glutathione (GSH) levels. The effects on protein expression patterns depending on pesticide type and the tissue used for analysis were studied in parallel by 2-DE. In gill and nervous tissue about 2000 spots (pI 4-7) were resolved, with quite different expression patterns. Chlorpyrifos altered 72 proteins, mostly in nervous tissue, and carbaryl 35, distributed evenly between organs. Several specific spots were selected as specific protein expression signatures for chlorpyrifos or carbaryl exposure in gills and nervous tissue, respectively.
Keywords: Pesticide; Carboxylesterase; Acetylcholinesterase; Biomarkers; proteomic; two-dimensional gel electrophoresis